Study on physical and mechanical properties and freeze-thaw damage models of granite under freeze-thaw cycles - Xue, Song; Hu, Yongqiong; Jia, Chaojun; Wang, Liang (Frontiers in Built Environment, 2025)
IntroductionTo describe the evolution of freeze-thaw damage in rocks and quantitatively analyze the degree of damage, a freeze-thaw damage model based on continuum damage mechanics and thermodynamics is proposed.MethodsTaking granite as the research object, its physical and mechanical properties, acoustic emission characteristics, and failure modes were studied through freeze-thaw cycling, uniaxial compression, acoustic emission detection, and CT scanning experiments, and the validity of the model was verified.ResultsThe results show that with the increase in the number of freeze-thaw cycles, the porosity of the specimens significantly increases, while the uniaxial compressive strength, elastic modulus, and wave velocity of granite decrease exponentially. During uniaxial compression, the cumulative acoustic emission ring counts and energy increase in a stepwise manner. In the early stage of loading, the signals are few, but as the stress increases and the cracks propagate, the signals significantly increase and reach a maximum at the stress peak. An increase in the number of freeze-thaw cycles leads to a decrease in the rate of increase of ring counts and energy in the early stage of loading and a reduction in their cumulative values. The failure mode changes from “X”-shaped shear failure to conical shear failure, with the shear triangle gradually increasing and shifting upward, and the number of main cracks decreasing.DiscussionThe experimental results are consistent with the theoretical model, indicating that the model can accurately describe the mechanical behavior and damage evolution of rocks under freeze-thaw cycling.